Comparing Comprehension of a Long Text Read in Print Book and on Kindle: Where in the Text and When in the Story? - Mangen, Anne; Olivier, Gérard; Velay, Jean-Luc (Frontiers in Psychology, 2019)
Digital reading devices such as Kindle differ from paper books with respect to the kinesthetic and tactile feedback provided to the reader, but the role of these features in reading is rarely studied empirically. This experiment compares reading of a long text on Kindle DX and in print. Fifty participants (24 years old) read a 28 page (approx. one hour reading time) long mystery story on Kindle or in a print pocket book and completed several tests measuring various levels of reading comprehension: engagement, recall, capacities to locate events in the text and reconstructing the plot of the story. Results showed that in most tests subjects performed identically whatever the reading medium. However, on measures related to chronology and temporality, those who had read in the print pocket book, performed better than those who had read on a Kindle. It is concluded that, basically comprehension was similar with both media, but, because kinesthetic feedback is less informative with kindle, readers were not as efficient to locate events in the space of the text and hence in the temporality of the story. We suggest that, to get a correct spatial representation of the text and consequently a coherent temporal organization of the story, readers would be reliant on the sensorimotor cues which are afforded by the manipulation of the book.